Correction: Trishkin, M., et al. Assessment of a Company’s Due Diligence System against the EU Timber Regulation: A Case Study from Northwestern Russia. Forests 2015, 6, 1380–1396 - Maxim Trishkin (Forests, 2016)
The authors wish to make the following corrections to this paper [1]: The authors would like to apologize for any inconvenience caused to the readers by these changes.[...]